Research on the System of Keyway Geometrical Deviation Control - Li Zhaogang; Dong Jianfeng; Zhu Rupeng (Jixie chuandong)
To improve the standard system of key connection in China, the research was carried out from 4 aspects to ensure the level of the system, innovation and perfection. Firstly, the control principle and basic principle of keyway geometrical deviation were presented. Then, the principles of "choosing different detection methods according to application needs" and "determining the datum embodiment method according to detection methods" were put forward. The basic terms were agreed, and five new features such as detection value, one-way measurement value, two-way measurement value, conventional measurement method and precision measurement method were added. Then, 7 kinds of optional control indicators were set up, and a clear boundary definition of each indicator was made. The concrete method of datum embodiment and definition of relevant terms were given. Finally, the Chinese reference translations of the English entries of three important features in the national geometrical tolerance standard were given, and the definition symbol of symmetry tolerance was changed from t to 2t.